Associated Biochemical Changes and Outcome of Acute Kidney Injury in ICU Patients and Impact on Rifle Classes - Ul Islam, Syed Mahtab; Arjumand, Marina; Huda, Md Nurul; Kamal, Rosanna Bintey; Haider, MS (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Acute Kidney Injury (AKI) has an independent impact on outcome, even after correction of all other variables in critically ill patients . AKI in ICU is often associated with different biochemical metabolic derrangements as a result of sepsis and non-renal organ system failure. Adequate informations are essential to develop effective measures to prevent and control morbidity and mortality. This study was done to detect AKI with their associated biochemical abnormalities and outcome among admitted patients in intensive care unit of BSMMU. Materials and methods: This prospective observational study was carried out in the Department of Nephrology, Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka, during the period of September 2015 to October 2016. A total of 105 patients who were admitted in the Department of Anesthesia, Analgesia and intensive care medicine, BSMMU were included in this study. Patients who had pre-existing CKD, those on maintenance dialysis, with history of renal transplantation, Feature suggestive of chronic kidney disease were excluded. Baseline data were recorded accordingly. The study population was divided initially into two group (No AKI and AKI) then sub groups into risk, injury, failure and followed up till discharge or death. Results: Incidence of AKI was 37.14%. Mean increase in Serum creatinine was 64.53%, 132.87% and 375.01% from baseline for risk, injury and failure respectively. Subgroup analysis revealed risk (20%) injury (6.67%) and failure (10.47%). Associated acid base disorder, electrolytes imbalance, hepatic dysfunction, haemotogical disorder and hypoalbuminemia were found statistically significant between two groups. Logistic regression analysis showed that associated haematological abnormalities were positively correlated to the development of AKI. But among these no variables showed significant effect on RIFLE class population. Our study revealed overall morality is (53.8%). Mortality was highest in Failure class and most patients from risk class achieved renal recovery. Conclusion: The incidence of AKI in critically ill patient is high. Associated biochemical changes should be addressed properly to minimize fatality. RIFLE classification for AKI might help in recruitment of patients for predicting prognosis. JCMCTA 2021 ; 32 (2) : 53-58